Переописание червецов рода псилококкус - Psylococcus Borschs. (Homoptera, Coccoidea) - фауны СССР - Терезникова, Е.М. (Вестник зоологии, 1967)
Studying the materials of Zoology Institute, Academy of Sciences of the USSR and basing on the author's own collections, a redescription of the genus Psilococcus Borchs. with two previously known species is made, drawings and a determining table being presented. The determining table of the genus Psilococcus B o r c h s. species. 1(2) A sublateral stripe of the quinquelocular glands is wide; on the breast being of 8-9 gland width. P. ruber Borchs. 2(1) A sublateral stripe of the quinquelocular glands is narrow; on the breast being of 3-6 gland width. P. porous Borchs